2006
DOI: 10.1079/asc200644
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and muscle characteristics of beef cull cows between 4 and 9 years of age

Abstract: The effects of age and breed on carcass and muscle characteristics of cull cows slaughtered at the same fattening state between 4 and 9 years of age were analysed in four French breeds: Aubrac (AU), Charolais (CH), Limousin (LI), and Salers (SA). Muscle characteristics were determined in three muscles: longissimus thoracis (LT), semitendinosus (ST) and triceps brachii (TB). They included: (1) the % frequency, cross-sectional area and % area of the different fibre types classified according to their contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 22 publications
3
33
1
Order By: Relevance
“…Higher total collagen contents were reported for bulls compared to steers (Cross et al, 1984b) and for bulls compared to cows of the same breeds (Jurie et al, 2005(Jurie et al, , 2006, apparently due to the effect of different testosterone levels. This supports our finding that the MLL samples of heifers contained less total collagen than those of bulls.…”
Section: Discussionmentioning
confidence: 88%
“…Higher total collagen contents were reported for bulls compared to steers (Cross et al, 1984b) and for bulls compared to cows of the same breeds (Jurie et al, 2005(Jurie et al, , 2006, apparently due to the effect of different testosterone levels. This supports our finding that the MLL samples of heifers contained less total collagen than those of bulls.…”
Section: Discussionmentioning
confidence: 88%
“…The 2 skeletal muscles analyzed in this study vary widely in muscle characteristics including muscle fiber type. Jurie et al (2006) showed that the STN had a greater percentage of fasttwitch glycolytic fibers, whereas the LM had a greater percentage of slow-twitch oxidative fibers. Muscle fiber types are dynamic, constantly changing in proportion as the animal ages, but muscle type is a reflection of the energy requirements of the muscle (Hocquette et al, 1998;Oddy et al, 2001).…”
Section: Fatty Acid Compositionmentioning
confidence: 94%
“…However, this practice is expensive for what it is generally obtained from one muscle only, being longissimus thoracis et lumborum the most common reference muscle. Other muscles represent different anatomical regions and divergent functionalities (postural and motor muscles), which may affect their fatty acid profile (Costa et al, 2008;Jurie et al, 2006;Lefaucheur et al, 2006;Hocquette, 2006).…”
Section: Introductionmentioning
confidence: 99%